Advanced biomaterials in pressure ulcer prevention and care: from basic research to clinical practice - Tian, Shaoqiang; Bian, Wei (Frontiers in Bioengineering and Biotechnology, 2025)
Pressure ulcers are a common and serious medical condition. Conventional treatment methods often fall short in addressing the complexities of prevention and care. This paper provides a comprehensive review of recent advancements in advanced biomaterials for pressure ulcer management, emphasizing their potential to overcome these limitations. The study highlights the roles of biomaterials in enhancing wound healing, preventing infections, and accelerating recovery. Specific focus is placed on the innovation and application of multi-functional composite materials, intelligent systems, and personalized solutions. Future research should prioritize interdisciplinary collaboration to facilitate the clinical translation of these materials, providing more effective and tailored treatment approaches. These advancements aim to improve the quality of life and health outcomes for patients by offering more reliable, efficient, and patient-specific therapeutic options.